Female Sports Journalists: The More Things Change, the More They Stay the Same - Aage Radmann; Anna Sätre (Media and Communication, 2024)
This article aims to explore the experiences of female sports journalists in Sweden from a gender perspective. The theoretical framework is inspired by Yvonne Hirdman’s understanding of gender in a binary system and R. W. Connell’s definition of hegemonic masculinity. Data consist of 10 semi-structured interviews with the most prominent female sports journalists in Sweden. The sports journalists in this study express that there has been a change in the media industry, resulting in a better understanding of women’s working conditions within the industry. Even so, the work is still grounded in a culture signified by hegemonic masculinity, where women need to find their own strategies to build a successful career, handle harassment, and cope with other gender-related challenges.